A telephone intervention to achieve differentiation in dietary intake: a randomized trial in paediatric primary care. Issue 6 (5th August 2016) - Rhodes, E. T.; Vernacchio, L.; Mitchell, A. A.; Fischer, C.; Giacalone, P.; Ludwig, D. S.; Ebbeling, C. B.
Summary: Background: Telehealth offers opportunities to extend clinical and research interventions for paediatric obesity. Objectives: To assess utility of a telephone intervention, implemented through a national primary care paediatric research network, for promoting differentiation in dietary intake, consistent with either a low‐glycemic load (Low GL) or Low Fat prescription, among overweight/obese school‐age children. Methods: Five‐week telephone dietary counselling intervention for parents of overweight/obese school‐age children recruited through the Slone Center Office‐based Research Network. Parent‐child dyads were randomized to Low GL or Low Fat diet. Primary outcomes were dietary GL and dietary fat, adjusted for energy intake and assessed by 24‐h dietary recall. Results: Subjects were randomized to Low GL ( n = 11, 8.1 ± 1.7 years, 45.5% male) or Low Fat ( n = 11, 8.2 ± 2.0 years, 36.4% male), with no baseline differences. Overall, 86% of subjects attended at least four of five counselling sessions, and study completion rate was 91% (based on completion of the final dietary recalls). Reported satisfaction was high. In adjusted analyses limited to 'recall completers, ' reduction in dietary GL (g/1000 kcal) achieved within the Low GL group was significant ( p = 0.01) and greater than the change in dietary GL in the Low Fat group (mean ± SE; −12.9 ± 4.4 vs. 5.1 ± 4.9, p = 0.03). Similarly, reduction in dietary fat (% of total energy) within the Low Fat group was significant (−5.6 ± 2.5, p = 0.046) but with no difference between groups ( p = 0.25). Conclusion: A telephone‐based dietary intervention for overweight/obese children, implemented through a national paediatric research network, fostered prescribed dietary changes. ClinicalTrials.gov registration: NCT00620152